Antibiotic profiling of Pseudomonas aeruginosa isolates from pus sample of rural tertiary care hospital of Western Maharashtra, Loni, India - Raytekar, Namita A.; Choudhari, Meghna R.; Das, Sonali (International Journal of Research in Medical Sciences, 2017)
Background: Pseudomonas aeruginosa (P. aeruginosa) considered as an opportunistic pathogen which can be isolated from various kinds of infection. The risk of emergence of antibiotic resistance is based on different antibiotic treatments. Antibiotic resistance and flexibility to adapt changing environment renders the pathogens a matter of concern in hospital acquired infections. Changing pattern of antimicrobial resistance pose challenge in treating pyogenic infections, hence periodical monitoring of bacterial profile and their antibiotic susceptibility pattern is important. This study deals with the infectious and drug resistance nature of P. aeruginosa with effectiveness of antimicrobial agents against it. Methods: Present study was conducted in Centre for Biotechnology, Pravara Institute of Medical Sciences, Loni, Maharashtra, India. A total of 763 pus samples were received in the bacteriology section of department of microbiology, rural medical college, Loni from the various wards of Pravara Rural Hospital. The colonial morphology and identification was done as per standard microbiology procedures. Antibiogram testing was done as per Kirby Bauer disc diffusion method. Results: Out of 763 pus samples 154 were Pseudomonas aeruginosa thus showing 20.19% prevalence. In this study, it was observed that isolates were sensitive to Ciprofloxacin (76.63%) followed by Amikacin. However, showed 90.90 % resistant to Cefazolin followed by Co-trimoxazole 75.97% was observed. Multi drug resistance (MDR) strain 68.83% (N=106) was detected from 154 isolates strains of Pseudomonas aeruginosa. Prevalent resistance pattern was found to be GENr, AKr, CAZr, CZr, COTr for 10 (9.43%) isolates followed by GENr, CAZr, CZr, MRPr, COTr, CIPr for 9 (8.49%) isolates. Conclusions: Present study focused on antibiotic resistance pattern of P. aeruginosa from pus sample. This study contributes in understanding the emergence of MDR strains which can be considered for judicial usage of antibiotics in hospital settings.